ADVERTISING IMPACT ON THE MEDIA CONTENT â€“ CASE OF ALBANIA - Axhami, Mirdaim; Mersini, Mirela; Zela, Loreta Axhami (European Scientific Journal, ESJ, 2015)
One of the challenges faced by the Albanian media today is maintaining its independence in an environment in which the governmental or corporate advertising attempt (and in many cases succeed) to impose rules. Cracking of the â€œChinese Wallâ€ distinguishing the commercial from the media is just another form of the influence of advertising influence not only in traditional media but also to new ones. Media specialists consider sharing of content of the advertisements one of the main mechanisms guaranteeing editorial freedom and independence, which is very important not only for the media but also the development of society as a whole. Another problem in Albania involves lack of transparency on the data for advertising media market. No concerted efforts are observed on the side of the media industry neither to measure the audience nor to publish data on the advertising market. Market advertising problems are unknown and unexplained, in a situation lacking basic information upon which the â€œadvertising cakeâ€ is logically divided. However, the fact that for most of the Albanian governmental and large corporations media advertising are the main source of income, shows how easy it can influence the editorial policies. This study focuses on the relationship among advertising and journalism; characteristics and impacts of these reports on the quality of journalism. In order to conclude this research, we utilized empirical data, media content analysis and interviews conducted with journalists and the most influential media editors in chiefs of media in the country